Liver injury under chronic viral hepatitis C against the background of opiomania: morphological characters - Ye. V. Beloborodova; D. V. Podgornova; I. L. Purlik; E. I. Beloborodova; L. A. Petrova; M. M. Volchanovskaya; S. G. Shkorlupa; I. A. Goncharova; O. Ye. Akbasheva (Бюллетень сибирской медицины)
To ascertain the severity of opium-induced liver injury for chronic viral hepatitis C (HCV) patients with detection of morphological characters of hepatocyte impact by opiates.Needle biopsy of liver and the light microscopy of biopsy material were made both for isolated HCV and HCV+opiomania patients.Liver injury (hepatitis activity, fibrosis stage) for HCV patients against the background of opiomania does not differ from the case of isolated HCV. Use of alcohol by opium addicts even in very small doses (10—15 g per day) cause the development of significantly more severe liver injury. Fibrosis of central vein was found significantly more often for HCV against the background of opiomania.Fibrosis of central vein is a differential-diagnostic criterion of being opiates as an etiological factor of liver injury. Opiates as an isolated toxic factor does not cause severe liver injury for HCV patients unlike the use of alcohol even in small doses.